2021
DOI: 10.3390/cells10112936
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin and Cold Atmospheric Plasma Synergize to Trigger Distinct Cell Death Mechanisms and Immunogenic Responses in Glioblastoma

Abstract: Targeting the redox balance of malignant cells via the delivery of high oxidative stress unlocks a potential therapeutic strategy against glioblastoma (GBM). We investigated a novel reactive oxygen species (ROS)-inducing combination treatment strategy, by increasing exogenous ROS via cold atmospheric plasma and inhibiting the endogenous protective antioxidant system via auranofin (AF), a thioredoxin reductase 1 (TrxR) inhibitor. The sequential combination treatment of AF and cold atmospheric plasma-treated PBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 53 publications
4
53
0
2
Order By: Relevance
“…The differences in sensitivity to each of the compounds observed between particular cell lines most likely result from the aforementioned biodiversity of cell lines used in this study. Indeed, several groups have documented a differential response of those three cell lines to various therapeutic approaches [ 55 , 56 , 57 , 58 ]. Here, compared to T98G and LN229 cells, U87MG cells turned out to be less susceptible to dendrimer-mediated toxicity, which was particularly pronounced in colony-forming assay.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in sensitivity to each of the compounds observed between particular cell lines most likely result from the aforementioned biodiversity of cell lines used in this study. Indeed, several groups have documented a differential response of those three cell lines to various therapeutic approaches [ 55 , 56 , 57 , 58 ]. Here, compared to T98G and LN229 cells, U87MG cells turned out to be less susceptible to dendrimer-mediated toxicity, which was particularly pronounced in colony-forming assay.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Deben et al 59 reported induction of ICD in glioblastoma cells via perturbation of ROS homeostasis through sequential combinatorial treatment of auranofin ( AF , Fig. 20) and cold atmospheric plasma treated phosphate buffered saline (pPBS).…”
Section: Metal Based Complexes As Icd Inducersmentioning
confidence: 99%
“…It has been reported that CAP-derived RONS (especially OH•) can be transported to millimeter depths to reach deep-seated diseased cells [237]. CAP has shown to induce a variety of biological effects, such as blood coagulation [238], tissue regeneration [237,239], sterilization [4,238,240], wound healing [15,228,238], cancer cell death [7,9,51,59,96,233,238,240,241], activation of immune cells [242,243], and virus inactivation [244,245]. The type and concentration of CAP-generated species delivered to cells depend on the CAP operating conditions, controlled by the design of the source, including the configuration of the electrodes.…”
Section: Cold Atmospheric Plasma (Cap)mentioning
confidence: 99%
“…These compounds induce cancer cell death by releasing electrons from the electron transport system (ETS) to O 2 by NADPH dehydrogenase, resulting in the formation of O 2 − . The oxidative stress caused by chemotherapeutic drugs interferes with cellular processes by changing the integrity of the cell membrane to cause cytotoxicity and thereby increasing their cytotoxic effect [7,51,243]. In addition, since some side effects caused by chemical agents appear to be prevented by certain antioxidants, administering these supplements during chemotherapy may diminish the development of side effects, as well as improve the response to therapy [256].…”
Section: Chemical Sourcesmentioning
confidence: 99%